2003
DOI: 10.1192/bjp.182.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Predicting engagement with services for psychosis: insight, symptoms and recovery style

Abstract: BackgroundTreatment non-adherence and service disengagement are commonly attributed to impaired insight. There is evidence that recovery style (i.e. psychological adjustment) may underlie service engagement.AimsWe examined whether insight, psychotic symptoms or individuals' recovery style (‘integration’ v. ‘sealing-over’) predicts service engagement.MethodFifty patients with schizophrenia were assessed during acute psychosis and at 3-month and 6-month follow-ups. Measures included recovery style, psychosis sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
151
5
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(176 citation statements)
references
References 20 publications
15
151
5
5
Order By: Relevance
“…This interpretation is supported by evidence suggesting that patients who seal over are those who see greater loss and shame in their psychosis, motivating denial (Staring et al, 2014;Tait et al, 2003). In our study no significant association was found between thought disorder and patients' subjective experiences of recovery as measured by the RAS subscales.…”
Section: Discussion Of the Resultssupporting
confidence: 71%
“…This interpretation is supported by evidence suggesting that patients who seal over are those who see greater loss and shame in their psychosis, motivating denial (Staring et al, 2014;Tait et al, 2003). In our study no significant association was found between thought disorder and patients' subjective experiences of recovery as measured by the RAS subscales.…”
Section: Discussion Of the Resultssupporting
confidence: 71%
“…Despite such findings, insight, as traditionally defined, has not always been related to either medication adherence (Trauer & Sacks, 2000), engagement in treatment (Tait, Birchwood, & Trower, 2003), or other beliefs about mental illness. In a cross-sectional study, Tait et al (2003) found that "recovery style, 1 " a construct that included the person's beliefs about the personal relevance of experiencing psychotic symptoms and whether the causes of symptoms are internal or external, predicted treatment engagement.…”
Section: Cognitive Appraisal and Copingmentioning
confidence: 93%
“…In a cross-sectional study, Tait et al (2003) found that "recovery style, 1 " a construct that included the person's beliefs about the personal relevance of experiencing psychotic symptoms and whether the causes of symptoms are internal or external, predicted treatment engagement. Individuals who took on a more "integrative" recovery style were more engaged in treatment; however, insight as traditionally defined was not associated with either recovery style or service engagement.…”
Section: Cognitive Appraisal and Copingmentioning
confidence: 99%
“…However, trauma severity was not related to self-blame cognitions or negative symptom severity. The former may be explained by the self-blame items being less frequently endorsed compared to the negative self and world items, and the latter may be attributable to an avoidant or ‘sealed-over’ coping style, whereby people with negative symptoms may be less likely to disclose traumatic events (Tait, Birchwood, & Trower, 2003). This finding is also in line with a recent systematic review (Bailey, Alvarez-Jimenez, Garcia-Sanchez, Hulbert, Barlow & Bendall, 2018) that found only childhood neglect was associated with negative symptoms.…”
Section: Discussionmentioning
confidence: 99%